SOLUTION: Ta có $n^3-19n=(n^3-n)-18n= n(n^2-1)-18n=n(n-1)(n+1)-18n$
Nhận thấy $n-1,n,n-1$ là ba số nguyên liên tiếp nên tồn tại ít nhất một số chia hết cho $2$ và ít nhất một số chia hết cho $3$. Mà $(2,3)=1$ nên $(n-1)n(n+1) \ \vdots 6$, và $18n \ \vdots 6$ nên $$n^3-19n \vdots 6$$
SOLUTION: Ta có $n^3-19n=(n^3-n)-18n= n(n^2-1)-18n=n(n-1)(n+1)-18n$
Nhận thấy $n-1,n,n-1$ là ba số nguyên liên tiếp nên tồn tại ít nhất một số chia hết cho $2$ và ít nhất một số chia hết cho $3$. Mà $(2,3)=1$ nên $(n-1)n(n+1) \ \vdots 6$, và $18n \ \vdots 6$ nên $$n^3-19n \vdots 6$$